In situ observation of NiS nanoparticles depositing on single TiO2 mesocrystal for enhanced photocatalytic hydrogen evolution activity - Shi, Xiaowei; Kim, Sooyeon; Fujitsuka, Mamoru; Majima, Tetsuro (Applied catalysis. B, Environmental, 2019)
[Display omitted] •Deposition of NiS on TiO2 mesocrystal (TMC) was in situ monitored via single-particle photoluminescence (PL) spectroscopy.•The variations of PL intensity and lifetime on individual TMC particle was detected before and after NiS photodeposition.•The interfacial electron injection kinetics from TMC to NiS in individual TMC/NiS particle was investigated.•TMC/NiS heterostructure exhibited 71 folds enhanced H2 evolution compared with TMC. For photocatalysis, clarifications of charge carrier migration route and kinetics on individual particles by photoluminescence (PL) are of great importance because they play significant roles on unveiling the precise information of structure-activity relationships and closely relate to the photocatalytic activities of those semiconductors on targeted functions. Here, photodeposition process of NiS nanoparticles on single TiO2 mesocrystal (TMC) as co-catalyst is in situ monitored by PL images and spectra using a confocal single-particle PL microscopy, which provides straightforward results on understanding the photoexcited electrons transfer in both individual TMC and TMC/NiS nanoparticles. Through the changes in PL intensity and decay lifetime, preferential trapping site for NiS nanoparticles on TMC is identified and efficient electron interfacial migration from TMC to NiS nanoparticles is demonstrated, which lead to an almost 71 folds enhancement on the photocatalytic H2 evolution under 365-nm photoirradiation compared to pure TMC particles.